Comparative Analysis of Public Service Quality Between Private Organizations and Public Organizations - Nurul Aida Lestari; Eli Apud Saepudin; Widya Nurfitriani; Linda Aulia; Ima Muslimah; Siti Najla Destria (Journal of Politica Governo, 2024)
A comparative analysis of the quality of public services between private organizations and public organizations is a study that aims to determine H the differences in the quality of services provided by private organizations R and public organizations. In this study, service quality is influenced by R various factors, such as organization, leadership, abilities and skills, A appreciation and public knowledge of public services. This analysis will display the results of measuring public satisfaction with public services, which is measured using the Public Satisfaction Index (IKM). From this research, it is expected that several conclusions will emerge regardingthe quality of public services provided by private organizations and public organizations, as well as the factors that influence the quality of public services. This research will assist the government and public organizations in improving the quality of public services, so as to increase public satisfaction with the public services provided. In addition, this research will also be a reference for private organizations in improving the quality of services provided to the community